Quantifying training load and intensity in elite male ice hockey according to game-related contextual variables - Rago, V.; Mohr, M.; Vigh-Larsen, J. F. (Biology of Sport, 2023)
We aimed to quantify training load (TL) and intensity during practice sessions according to game-related contextual variables (game outcome, opponent standard, game location) in an elite male ice hockey team. Practice data were collected using a wearable 200-Hz accelerometer, heart rate (HR) recording, and session-rating of perceived exertion (s-RPE) throughout 23 sessions (n = 306 files). The reference team performed a greater number of accelerations, decelerations, spent longer time > 85% maximum HR (t85%HRmax) and reported greater s-RPE after losing a game compared to a win (r = 0.13-0.19). Moreover, a lower number of accelerations, decelerations, t85%HRmax and s-RPE (r = 0.15-0.45) were found before playing against a top-ranked opponent. In contrast, more accelerations, decelerations, longer t85%HRmax and greater s-RPE were observed after playing against a top-ranked team opponent (r = 0.15-0.41). The players performed more accelerations/min, spent more t85%HRmax and reported greater s-RPE before playing an away game (r = 0.13-0.22). Weekly TL seems to slightly increase after losing a game, when preparing a game against a weaker opponent, after playing against a stronger opponent, and when preparing an away game. On the other hand, training intensity seems not to be affected by game-related contextual variables. Thus, ice hockey practitioners involved with TL monitoring should consider the interplay of the numerous variables that influence the volume of prescribed training and the actual training responses in each individual player.